If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 19 = 47 Reorder the terms: 19 + x = 47 Solving 19 + x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + x = 47 + -19 Combine like terms: 19 + -19 = 0 0 + x = 47 + -19 x = 47 + -19 Combine like terms: 47 + -19 = 28 x = 28 Simplifying x = 28
| 7x+-8=34 | | =(4x+3)(2x-3) | | 2(3a+4)=3a+2 | | -4(x+5)-x-3=-5(x+2)-13 | | -4(x+5)-x-3=-5(x+2)-133 | | -4(x+5)-x-3=-5(x+2)+3 | | 4a+4=3a+-4 | | 0=4x^2+5x+9 | | 26x-18=25x+18 | | x^3/2x=-343 | | 0=4x^2+9x+7 | | 100p+10=p+15 | | 100p+10=100p+15 | | 9v+11=9v-4 | | 3x/4=5/7 | | x(x-7)=x^2+112 | | 4+t^2=68 | | .15x+.08(140-x)=-.15x | | h/h | | d^2=1 | | a^2-16=48 | | 3b^2-7=68 | | (2x+3)=2 | | x/5-10=30 | | y-4=0(0-0) | | -10(14x+15)+x=2x-10 | | 4y^2-21y=18 | | 2(y+1)(y+3)=16 | | (y-1)(y+6)-8=0 | | (x-2)(x-2)+(3x+1)(3x+1)-(2x+1)(2x-1)-(2x+3)(2x+3)=0 | | 200(1+0.07/1)^3 | | (y+3)(y+4)=2 |